Diagnostic Accuracy of Inflammatory Markers As Early Predictors of Infection After Elective Colorectal Surgery: Results From the IMACORS Study. Issue 5 (May 2016) - Facy, Olivier; Paquette, Brice; Orry, David; Binquet, Christine; Masson, David; Bouvier, Aurélie; Fournel, Isabelle; Charles, Pierre E.; Rat, Patrick; Ortega-Deballon, Pablo
Abstract : Background: Intra-abdominal infections are frequent and life-threatening complications after colorectal surgery. An early detection could diminish their clinical impact and permit safe early discharge. Objective: This study aimed to find the most accurate marker for the detection of postoperative intra-abdominal infection and the appropriate moment to measure it. Methods: A prospective, observational study was conducted in 3 centers. Consecutive patients undergoing elective colorectal surgery with anastomosis were included. C-reactive protein and procalcitonin were measured daily until the fourth postoperative day. Postoperative infections were recorded according to the definitions of the Centres for Diseases Control. The areas under the receiver operating characteristic curve were analyzed and compared to assess the diagnostic accuracy of each marker. Results: Five-hundred and one patients were analyzed. The incidence of intra-abdominal infection was 11.8%, with 24.6% of patients presenting at least one infectious complication. Overall mortality was 1.2%. At the fourth postoperative day, C-reactive protein was more discriminating than procalcitonin for the detection of intra-abdominal infection (areas under the ROC curve: 0.775 vs 0.689, respectively, P = 0.03). Procalcitonin levels showed wide dispersion. For the detection of all infectious complications, C-reactive protein was also significantly more accurate than procalcitonin on the fourth postoperative day (areas under the ROC curve: 0.783 vs 0.671, P = 0.0002). Conclusions: C-reactive protein is more accurate than procalcitonin for the detection of infectious complications and should be systematically measured at the fourth postoperative day. It is a useful tool to ensure a safe early discharge after elective colorectal surgery.